The Impact of Online Registration Systems on Patient Satisfaction and Outpatient Service Delivery: A Scoping Review - Ninung Rose Diana Kusumawati; Bagoes Widjanarko; Sutopo Patria Jati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Online registration systems have emerged as digital innovations to improve the efficiency of outpatient services, which often experience long queues and extended waiting times that negatively affect patient satisfaction. By enabling remote appointment scheduling, these systems aim to streamline administrative processes and enhance healthcare delivery. This scoping review followed the PRISMA 2020 guideline to identify studies published between 2015 and 2025 examining the implementation of online or electronic registration systems in hospital outpatient settings. Searches were conducted across PubMed, Google Scholar, and EbscoHost, including English and Indonesian articles. A total of 2,148 abstracts were screened, and data were extracted on study design, system type, outcomes, and key findings related to waiting time and patient satisfaction. Ultimately, six studies were included. Each study was independently reviewed by two reviewers, and in cases of disagreement, a third reviewer was consulted to reach a consensus. Six studies from Indonesia and India met inclusion criteria. Most used quantitative designs, while one employed a qualitative approach. All studies reported significant reductions in waiting time (up to 75%) and improvements in patient satisfaction, driven by ease of access, reduced congestion, and system responsiveness. Integration with hospital information systems enhanced adoption, although barriers such as low digital literacy and technical limitations persisted. Online outpatient registration systems effectively reduce waiting times and improve satisfaction, supporting their integration into hospital digital transformation strategies.